Indocyanine green fluorescence-guided laparoscopic central pancreatectomy for complete pancreatic transection trauma: a rare case and literature review - Wang, Xitao; Teng, Xiong; Liu, Yi; Cheng, Wei (Frontiers in Surgery, 2025)
BackgroundPancreatic trauma is a rare solid organ injury. Conservative treatment is often indicated in patients with no pancreatic duct injury, while patients with high-grade pancreatic damage most often require surgical intervention. Laparoscopic central pancreatectomy (LCP) is a parenchyma-sparing approach and can prevent endocrine and exocrine insufficiency after pancreatic resection. Indocyanine green (ICG) fluoroscopy can help the surgeon assess the blood supply of the target organ.Case presentationThe case we describe here is a 33-year-old male patient who was transferred to our hospital due to blunt abdominal trauma caused by a car accident. The patient was hemodynamically stable on admission and was diagnosed with isolated pancreatic trauma by a multidisciplinary team that included radiologists, emergency physicians, and pancreatic surgeons. The patient then underwent emergency laparoscopic central pancreatectomy, during which we used ICG fluoroscopy to assess the blood perfusion of the damaged pancreas to determine the extent of resection. The patient developed a biochemical fistula (grade A pancreatic fistula) after surgery, and no other intervention was performed except for continuous drainage. The patient was discharged on postoperative day 13. At the 3-month follow-up, the patient did not present any clinical manifestations of pancreatic endocrine and exocrine insufficiency.ConclusionTo the best of our knowledge, there have been no reports of ICG-guided emergency LCP for blunt abdominal trauma. In selected patients, emergency LCP is feasible and should be supported by a multidisciplinary team and performed by an experienced pancreatic surgeon with advanced laparoscopic skills.